The Question of Islamophobia and Marlowe's Tamburlaine the Great - Al-Abboud, Dalia (AUC Knowledge Fountain, 2016)
In my thesis, I exam the way the Islamic religion had been attacked and negatively portrayed in European literature for centuries after the advent of this monotheistic religion under Prophet Mohammed’s flag in the Arabian Peninsula. Islam was demeaned and its culture was distorted as a means of building upon Christian confidence in the face of the sophisticated faith of Islam, which was spreading with surprising speed (represented by the Ottoman Empire) in Christian Europe. I look at different European examples of the negative portrayals of Islam before focusing specifically on English Renaissance writers generally and Christopher Marlowe specifically as a representative of his era. By closely examining Marlowe’s Tamburlaine the Great we are enabled a deeper understanding of the way Islam was looked at with fear and grudging respect in sixteenth century England. By understanding the status of Islam and its past reception in European Christendom, we reach a better understanding of modern Islamophobia in its current form; only by attempting to re-read the past can we understand the present.